2016
DOI: 10.1111/rda.12802
|View full text |Cite
|
Sign up to set email alerts
|

Semen supplementation with palmitoleic acid promotes kinematics, microscopic and antioxidative parameters of ram spermatozoa during liquid storage

Abstract: The purpose of the present experiment was to investigate the protective effects of palmitoleate on the quality of ram semen during low temperature liquid storage. Ejaculates were collected using the artificial vagina from four Qezel rams twice a week. Ejaculates were pooled, diluted with Tris-egg yolk extender without palmitoleate (control) or supplemented with 0.125 (P 0.125), 0.25 (P 0.25), 0.5 (P 0.5) and 1 (P 1) mM palmitoleate at a final concentration of 500 × 10 spermatozoa/ml. Total motility and forward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 43 publications
1
21
0
Order By: Relevance
“…The efficiency of TL-HEPES and PBS in sperm processing (16,17) and in short-term storage (18)(19)(20) was identified in previous studies. Tris-citrate is a commonly used extender (1), and it is also usually used as the control or main extender in ram sperm-extender studies (21)(22)(23)(24). TEST, TL-HEPES, and PBS extenders were found to be effective in protecting the sperm against cold shock when freezing rat sperm and in equilibration at 4 °C (20,25).…”
Section: Introductionmentioning
confidence: 99%
“…The efficiency of TL-HEPES and PBS in sperm processing (16,17) and in short-term storage (18)(19)(20) was identified in previous studies. Tris-citrate is a commonly used extender (1), and it is also usually used as the control or main extender in ram sperm-extender studies (21)(22)(23)(24). TEST, TL-HEPES, and PBS extenders were found to be effective in protecting the sperm against cold shock when freezing rat sperm and in equilibration at 4 °C (20,25).…”
Section: Introductionmentioning
confidence: 99%
“…Reports have shown that ram semen enrichment with butylated hydroxytoulene, taurine, catalase, quercetin, palmitoleic acid, and kinetin enhances motility or viability compared to the control when stored as liquid at refrigerator or after freeze‐thawing process (Banday et al, ; Câmara et al, ; Eslami et al, ; Rather et al, ; Zadeh Hashem & Eslmi, ). The results of the present experiment indicated that Id at 1, 2 and 4 µM enhanced total motility, FPM, and VCL at 48 and 72 hr of storage.…”
Section: Discussionmentioning
confidence: 99%
“…Reports have shown that ram semen enrichment with butylated hydroxytoulene, taurine, catalase, quercetin, palmitoleic acid, and kinetin enhances motility or viability compared to the control when stored as liquid at refrigerator or after freeze-thawing process (Banday et al, 2017;Câmara et al, 2011;Eslami et al, 2017;Rather et al, 2016;Zadeh Hashem & Eslmi, 2018 experiment. Previous study revealed a correlation between capacities of spermatozoa in fertilization with spermatozoa motility assessed by CASA (Larsen et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we have not yet had the opportunity to test this hypothesis directly in crocodile spermatozoa, we did secure several lines of correlative evidence that these cells use a similar metabolic strategy. Thus, capacitated crocodile spermatozoa experienced a selective depletion of palmitoleic acid [a monounsaturated fatty acid substrate known to enhance the motility profile of spermatozoa from species as diverse as sheep and fowls (35,36)], as well as a significant reduction in motility following the uncoupling of oxidative phosphorylation. Moreover, we identified CPT1A as a substrate for differential phosphorylation in noncapacitated versus capacitated crocodile spermatozoa.…”
Section: Molecular and Cellular Proteomics 1813 S73mentioning
confidence: 99%